Features of the Blood Pressure Variability of Athletes with Different Levels of Functional State of the Body - Romanchuk, Alexander P; Guzii, Oksana V (Journal of Education, Health and Sport, 2019)
To determine the features of the distribution of the parameters of the systolic (SBPV) and diastolic (DBPV) blood pressure variability dependent on the level of functional state (FS) of the athletes’ body "Spiroarteriocardiorhythmograph" was used. 104 male athletes, at the age of 20.6 ± 0.9, who were engaged in various sports, were analyzed. Taking into account the level of the FS, they were divided into 3 groups: the first group with a high level of FS was 39 people (“high”), the second group was 46 (“average”), the third group was 19 (“low”). This report analyzes the differences in the ranks of the parameters of the SBPV and DBPV – TPSBP (mmHg2), VLFSBP (mmHg2), LFSBP (mmHg2), HFSBP (mmHg2), LF/HFSBP (mmHg2/mmHg2), TPDBP (mmHg2), VLFDBP (mmHg2), LFDBP (mmHg2), HFDBP (mmHg2), LF/HFDBP (mmHg2/mmHg2) There were no possible differences in any registered SBPV values. We can speak about the reducing tendency in regulatory influences in all frequency grades, with the exception of high-frequency ones (HFSBP mmHg2), which is invalid tendency. After analyzing the DBPV data it becomes clear that in terms of VLFDBP (mmHg2) possible differences between “high” and “low” are quite pronounced. The analysis of the distribution ranks of the SBPV and DBPV parameters showed that the data on the measurement of the blood pressure variability in ultra-short measurements allows a sufficiently clear differentiation of the “low” level of FS, which is characterized by an increase in the total power of regulatory influences on the SBP due to supra-segmental effects and sympathetic effects, as well as an increase in low-frequency effects on DBP.